2005
DOI: 10.1677/joe.1.05969
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone-induced negative feedback mechanisms within the hypothalamo–pituitary–adrenal axis of the chicken

Abstract: This paper reports the results of in vivo and in vitro experiments on the feedback effects of corticosterone on the hypothalamo-pituitary-adrenal axis in embryos at day 18 of incubation and in 9-day-old chickens. In vivo, a significant negative feedback was detected on the levels of corticotropin-releasing factor (CRF) precursor (proCRF) mRNA and on the plasma concentration of corticosterone, two hours after a single intravenous injection with 40 µg corticosterone. In contrast, the levels of CRF peptide in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 47 publications
1
22
0
2
Order By: Relevance
“…Administration of exogenous CORT is known to down-regulate the endogenous CORT production in birds over a prolonged period (Vandenborne et al, 2005;Busch et al, 2008;Müller et al, 2009). Two 25mm Silastic implants significantly elevate baseline CORT levels in black-legged kittiwakes during the first 3days after implantation (Kitaysky et al, 2001;Angelier et al, 2007;Angelier et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Administration of exogenous CORT is known to down-regulate the endogenous CORT production in birds over a prolonged period (Vandenborne et al, 2005;Busch et al, 2008;Müller et al, 2009). Two 25mm Silastic implants significantly elevate baseline CORT levels in black-legged kittiwakes during the first 3days after implantation (Kitaysky et al, 2001;Angelier et al, 2007;Angelier et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the increase in blood CORT level may inhibit synthesis and secretion of corticotrophin-releasing hormone (CRH) and/or ACTH at the hypothalamic and hypophyseal levels, respectively. It has been shown that in chickens the glucocorticoid feedback becomes functional already between E15 and E18 [33,34]. Since in birds CRH is a potent stimulator of TSH secretion [35,36], it cannot be excluded that the decrease in T 4 secretion from the thyroid gland following RF-EMF exposure of the chicken embryo is accelerated not only by a negative effect of CORT on thyroid hormone synthesis but is also associated with inhibitory effect of CORT at the hypothalamic level.…”
Section: Discussionmentioning
confidence: 99%
“…The observed effects of cortisol on immunoreactive ACTH in the pituitary of chicken embryos suggest that negative feedback of adrenal glucocorticoids on pituitary ACTH release is already functional on day 11 (Kalliecharan & Buffett, 1982). A 2-hour in vitro CORT treatment of pituitaries taken from 17-day-old embryos caused a marginal decrease in hypophyseal POMC mRNA levels (Vandenborne et al, 2005). The presence of glucocorticoid receptor (GR) and mineralocorticoid receptor (MR) mRNA in the pituitary gland of chick embryos Kwok et al, 2007) may also point towards the existence of a negative feedback effect of glucocorticoids at the level of ACTH synthesis or release, though it has not been shown yet that these receptors are expressed by the corticotropes, let alone that they interact with ACTH synthesis, processing or secretion.…”
Section: Feedback Interactionsmentioning
confidence: 91%
“…The predominant cause of the increased thyroidal activity during the last week of embryonic development may be an elevated hypothalamic top-down stimulation. Both TRH and CRH levels in the hypothalamic region of the brain increase steadily towards hatching (Geris et al, 1999b;Vandenborne et al, 2005) and the decreasing CRH content of the median eminence towards day 19 is suggestive for an increased CRH secretion (Vandenborne et al, 2005). However, the role of endogenous TRH and CRH in the control of TSH (Burt & White, 2007;Cogburn et al, 2007) and has reconfirmed the chicken as an exceptional model organism in developmental biology (Stern, 2005;Davey & Tickle, 2007).…”
Section: Endocrine Events In the Last Week Of Embryonic Developmentmentioning
confidence: 99%